2022
DOI: 10.3389/sjss.2022.10438
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH, Humic Acids, and Salts on the Dissipation of Amoxicillin and Azithromycin Under Simulated Sunlight

Abstract: This work is focused on the study of the dissipation of the antibiotics amoxicillin (AMX) (an amino penicillin) and azithromycin (AZT) (belonging to the macrolide group), performed at a laboratory scale, under simulated sunlight and in the dark, at pH values 4.0, 5.5, and 7.2, and in the presence of humic acids and different inorganic salts. The results indicate that AMX is more affected than AZT by simulated sunlight, with half-lives ranging 7.7–9.9 h for AMX and 250–456 h for AZT. The lowest half-life values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This process will depend on multiple factors of the antibiotics, such as their log K OW , pK a , ionisation state, binding properties and buffering conditions (Tran et al, 2018;Jodeh et al, 2022). The pH of the medium will play a fundamental role in the different process in soil like degradation (Rodríguez-López et al, 2022a) or mainly in adsorption and will clearly influence its fate since antibiotics tend to behave differently depending on the pH, as they are amphoteric molecules, which can behave as anions, zwitterions, or cations. The pH not only influences the solubility and behaviour of the compounds but also the characteristics of the sorbent and can change the interactions between the contaminant and the sorbent (Anuar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This process will depend on multiple factors of the antibiotics, such as their log K OW , pK a , ionisation state, binding properties and buffering conditions (Tran et al, 2018;Jodeh et al, 2022). The pH of the medium will play a fundamental role in the different process in soil like degradation (Rodríguez-López et al, 2022a) or mainly in adsorption and will clearly influence its fate since antibiotics tend to behave differently depending on the pH, as they are amphoteric molecules, which can behave as anions, zwitterions, or cations. The pH not only influences the solubility and behaviour of the compounds but also the characteristics of the sorbent and can change the interactions between the contaminant and the sorbent (Anuar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there are several studies that have evaluated the toxicity of heavy metals in soil microbial communities (Hattori, 1992;Giller et al, 1998;Giller et al, 2009;Abdu et al, 2017). On the other hand, there are also previous studies focused on studying the effects of antibiotics on soil microorganisms (Thiele-Bruhn, 2005;Toth et al, 2011;Caban et al, 2018;Urra et al, 2019), however, there are few studies that focus on the study of tetracyclines in soil bacterial communities, such as Santás-Miguel et al (2020a); Santás-Miguel et al, 2020c;Santás-Miguel et al, 2020d), or on the temporal evolution of various antibiotics affected by environmental conditions, such as Rodríguez-López et al (2022). On the other hand, several works evaluated the cotolerance to antibiotics of soil bacterial communities, at the functional and genetic level, in soils contaminated with heavy metals (Bååth, 1989;Berg et al, 2010;Oyetibo et al, 2010;Ji et al, 2012;Dickinson et al, 2019;Santás-Miguel et al, 2020b;Santás-Miguel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have detected antibiotic uptake in crops like carrot and barley (Eggen et al, 2011), corn, green onion and cabbage (Kumar et al, 2005), lettuce and radish (Bassil et al, 2013) and grass, corn and wheat (Conde-Cid et al, 2018). It has been shown that different antibiotics may also impact on the soil microbial biomass (Santás-Miguel et al, 2020), and that their degradation in the soil environment is affected by variables such as soil pH, humic acids and salts (Rodríguez-López et al, 2022), which could substantially change after sludge spreading.…”
Section: Introductionmentioning
confidence: 99%